2022
DOI: 10.1186/s12889-022-14383-3
|View full text |Cite
|
Sign up to set email alerts
|

Community networks of sport and physical activity promotion: an analysis of structural properties and conditions of cooperation

Abstract: Background: The importance of intersectoral cooperation networks among community organizations located in people’s immediate environments in addressing population health problems such as physical inactivity has come into focus in recent years. To date, there is limited evidence on how and why such networks emerge. Therefore, the aims of this study were (a) to analyze the structural properties and (b) to identify the conditions of cooperation in interorganizational community networks of sport an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…Lastly, Wolbring et al provide a detailed analysis of community sports networks, which we found analogous to our study’s focus on health promotion networks. Their analysis of structural properties and cooperation conditions within networks offers valuable parallels to our findings, where the structural aspects of networks (e.g., centrality, tie formation) were crucial in mediating health outcomes 31 . By drawing on these parallels, we further substantiate our model of network-driven health promotion.…”
Section: Discussionsupporting
confidence: 65%
“…Lastly, Wolbring et al provide a detailed analysis of community sports networks, which we found analogous to our study’s focus on health promotion networks. Their analysis of structural properties and cooperation conditions within networks offers valuable parallels to our findings, where the structural aspects of networks (e.g., centrality, tie formation) were crucial in mediating health outcomes 31 . By drawing on these parallels, we further substantiate our model of network-driven health promotion.…”
Section: Discussionsupporting
confidence: 65%
“…Extant implementation research frameworks have also predominantly focused on relationships among similar or peer organizations (e.g., healthcare organizations, social services providers) ( 5 , 14 ). Most published studies assessing external relationships primarily focus on links among peer organizations, such as formal implementation networks ( 17 ), quality improvement collaboratives ( 18 ), or organizations providing similar client services ( 19 21 ). The updated definition of the “partnerships and connections” construct in CFIR 2.0 helps expand the scope of external relationships to include collaboratives, professional societies, referral networks, community-academic partnerships, advocacy groups, and technical assistance organizations ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, various intra- and interorganizational public health networks were examined using social network analysis to visualize structural characteristics and cooperation processes, such as active living [ 54 56 ], cancer support [ 57 , 58 ], children’s health initiatives [ 59 , 60 ], community care [ 61 63 ], elderly care [ 64 – 66 ], HIV/AIDS service [ 67 ], injury prevention and control [ 68 ], mental health services [ 69 72 ], physical activity promotion [ 73 75 ], prevention of diabetes [ 76 ], tobacco control [ 77 – 80 ], and women’s health [ 81 , 82 ]. These public health networks differ in many ways from the network at hand, because they address the specific health needs and problems of other populations, have a different health-related focus and mission, geographic coverage, types of stakeholders, ways in which network members cooperate, availability and distribution of resources and funding, and political, cultural, and social context.…”
Section: Introductionmentioning
confidence: 99%